Characterization of Neurosarcoid Myelitis and Assessment of Treatment Response: A Multicenter Retrospective Study. (5th December 2022) - Balaban, Denis; Manzano, Giovanna; Ali, Ahya; Flanagan, Eoin; Aksamit, Allen; Redenbaugh, Vyanka; Clardy, Stacey; Samudralwar, Rohini; Agyei, Paunel; Zabeti, Aram; Baughman, Robert; Chwalisz, Bart; et al.
Abstract : Objective: To determine if initial treatment with corticosteroids plus steroid-sparing immunosuppressive therapy (IST) results in faster gadolinium contrast-enhancement resolution in neurosarcoid myelitis (NSM) than corticosteroid monotherapy (CSM). Background: Neurosarcoidosis is a rare cause of myelitis, treated initially with corticosteroids. Whether combination therapy of corticosteroids plus IST is more effective than CSM at disease onset is unknown. Design/Methods: We retrospectively reviewed cases of definite or probable NSM, defined by Neurosarcoidosis Consortium Consensus Group, in adults treated at six United States centers. We characterized clinicoradiographic features and treatment outcomes after NSM diagnosis. Treatment groups were defined as CSM, corticosteroids plus intermediate oral IST (methotrexate or mycophenolate mofetil), corticosteroids plus highly effective IST (cyclophosphamide/TNF-alpha inhibitors), or corticosteroids plus other. We hypothesized that initial treatment with corticosteroids and IST would result in faster gadolinium contrast-enhancement resolution (primary end point). Results: 63 patients with NSM (32 female, 30 definite, median age 48) were identified. 86% had spinal cord enhancement on post-gadolinium T1 sequences (8% without enhancement, 6% without data). Time from symptom onset to treatment initiation varied from 11 days to 10 years (median 4 months). All but one patient received corticosteroids initially. 16/63 received corticosteroids alone. 29/63 received corticosteroids and subsequently IST (10 TNF-alpha inhibitor/cyclophosphamide, 10 mycophenolate/methotrexate, 9 other). Median time to IST initiation was 9.1 months (range 1–132). 16/63 were treated with initial IST (4 TNF-alpha/cyclophosphamide, 8 mycophenolate/methotrexate, 4 other). There was no significant difference in time to contrast-enhancement resolution between corticosteroids with/without subsequent IST versus corticosteroids + initial IST (Wilcoxon-rank sum test 0.93) or CSM versus corticosteroids + initial IST (Wilcoxon-rank sum test 0.97). Limitations are small sample size, variations in initiation of treatment and doses used, and intervals of clinical/radiographic follow-up. Conclusions: Standardization of reporting and monitoring of treatment and outcomes is needed for patients with NSM to better assess optimal initial therapy plans.